Predictors of in-hospital mortality and attributable risks of death after ischemic stroke: The German Stroke Registers Study Group - Heuschmann, Peter U.; Kolominsky-Rabas, Peter; Misselwitz, Björn; Hermanek, Peter; Leffmann, Carsten; Janzen, R. W.C.; Rother, Joachim; Buecker-Nott, Hans Joachim; Berger, Klaus (Archives of internal medicine, 2004)
Background: There is a lack of information about factors associated with in-hospital death and the impact of neurological complications on early outcome for patients with stroke treated in community settings. We investigated predictors for in-hospital mortality and attributable risks of death after ischemic stroke in a pooled analysis of large German stroke registers. Methods: Stroke patients admitted to hospitals cooperating within the German Stroke Registers Study Group (ADSR) between January 1, 2000, and December 31, 2000, were analyzed. The ADSR is a network of regional stroke registers, combining data from 104 academic and community hospitals throughout Germany. The impact of patients' demographic and clinical characteristics, their comorbid conditions, and the treating hospital expertise in stroke care on in-hospital mortality was analyzed using Cox regression analysis. Attributable risks of death for medical and neurological complications were calculated. Results: A total of 13440 ischemic stroke patients were included. Overall in-hospital mortality was 4.9%. In women, higher age (P<.001), severity of stroke defined by number of neurological deficits (P<.001), and atrial fibrillation (hazard ratio [HR], 1.3; 95% confidence interval [CI], 1.0-1.6) were independent predictors for in-hospital death. In men, diabetes (HR, 1.3; 95% CI, 1.0-1.8) and previous stroke (HR 1.4; 95% CI, 1.0-1.9) had a significant negative impact on early outcome in addition to the factors identified for women. The complication with the highest attributable risk proportion was increased intracranial pressure, accounting for 94% (95% CI, 93.9%-94.1%) of deaths among patients with this complication. Pneumonia was the complication with the highest attributable proportion of death in the entire stroke population, accounting for 31.2% (95% CI, 30.9%-31.5%) of all deaths. More than 50% of all in-hospital deaths were caused by serious medical or neurological complications (54.4%; 95% CI, 54.396-54.5%). Conclusions: Substantial differences were found in the impact of comorbid conditions on early outcome for men and women. Programs aiming at an improvement in short-term outcome after stroke should focus especially on a reduction of pneumonia and an early treatment of increased intracranial pressure.
Created from Fastlane, Scopus look-up